Co-delivery of curcumin and piperine in zein-carrageenan core-shell nanoparticles: Formation, structure, stability and in vitro gastrointestinal digestion. (February 2020) - Chen, Shuai; Li, Qike; McClements, David Julian; Han, Yahong; Dai, Lei; Mao, Like; Gao, Yanxiang
Abstract: Core-shell biopolymer nanoparticles were fabricated using a hydrophobic protein (zein) as the core and a hydrophilic anionic polysaccharide (ι-carrageenan) as the shell. The outer layer was physically cross-linked using cationic calcium ions to form salt bridges between the anionic carrageenan molecules. The potential of using these core-shell nanoparticles to co-deliver two important nutraceuticals (curcumin and piperine) was also investigated. A combination of electrostatic attraction, hydrogen bonding, and hydrophobic interactions was shown to be responsible for the assembly of the curcumin-piperine-loaded nanoparticles. Low levels of calcium ions (0–2 mM) led to the formation of small nanoparticles with compact structures, whereas higher levels (2–5 mM) promoted particle aggregation. The structural organization and morphology of the core-shell nanoparticles also depended on calcium levels, as seen by changes in circular dichroism, fluorescence spectroscopy, and electron microscopy. The core-shell nanoparticles were shown to be effective at retarding the photo- and thermal-degradation of the encapsulated curcumin and piperine. In addition, the core-shell nanoparticles could delay the release of the nutraceuticals under in-vitro gastrointestinal conditions, which may improve their oral bioavailability. In summary, core-shell nanoparticles assembled from zein and ι-carrageenan may be effective co-delivery systems for curcumin and piperine. Graphical abstract: Image 1 Highlights: Co-delivery system nanoparticles with a shell of hydrogel were fabricated. Microtopography and secondary structure of zein in the nanoparticles were altered. Ca 2+ induced nanoparticles became better delivery vehicle of curcumin and piperine. Curcumin and piperine in nanoparticles exhibited better light and thermal stability. Ca 2+ induced nanoparticles delayed the release of nutraceuticals during in vitro digestion.